Development of a qPCR test to detect and quantify Elsinoë piri in unsprayed and organic apple orchards and assessment of apple cultivar susceptibility to the disease. (17th May 2022) - Chandelier, Anne; Mingeot, Dominique; Ghrissi, Ibtihel; Song, Jang Hoon; Lateur, Marc
Abstract: Recently, Elsinoë piri has become an important pathogen in unsprayed and organic apple orchards. The increasing demand for organic apples as well as the limited use of fungicides imposed by European legislation has turned this pathogen, which has been known for over a century in Europe, into a resurgent phytosanitary threat. It also represents a new trait to be taken into account in apple breeding programmes. As E . piri is extremely difficult to isolate and causes symptoms that can be confused with those caused by other pathogens, a quantitative PCR (qPCR) test has been developed based on the internal transcribed spacer (ITS) region of the rDNA gene. This test, which displays a low limit of detection, allows the early detection of the fungus in apple leaves. As a quantitative method, it is a promising tool for breeding purposes as it can be used on leaves to assess the level of quantitative resistance of apple cultivars to the disease. The molecular test is also useful to gain knowledge on the epidemiology of this re‐emerging fungal disease. Spore trapping conducted in 2015, 2016 and 2020 using Rotorod devices and the qPCR test showed that airborne inoculum is released at the end of the growing season. Tests were also carried out to demonstrate that the pathogen was detected in buds during winter. A comparison of 18 E . piri isolates based on the sequencing of five genome regions highlighted a high genotypic diversity. All these isolates were detected with the qPCR test developed in this study. Abstract : A qPCR test, developed for the detection of the pathogen Elsinoë piri, was used to gain knowledge on the disease (spore release period, primary inoculum, incubation period in leaves) and to assess the susceptibility of apple cultivars.